Three Level Cloud Storage Scheme for Providing Privacy Preserving using Edge Computing - Prof. I. Ramesh Babu, Vellalachervu Pavani (International Journal of Advanced Science and Technology, 2019)
With the rapid growth of unstructured data, cloud storage gets more and more attention for the advanced development.Inprimitive cloud storage schema, the entireuser’s data is totally stored into the centralized cloud servers. In other words, users lose their right of control on data and face privacy leakage risk .In this proposed thesis we developed a multi-layerapproach in order to store the sensitive data in a secure manner from the cloud server. Here we have integrated edge computing concept for the current cloud in which the data can be stored on a multiple edges rather than all the data in a centralized server. Here we try to divide the original data into multiple edges or blocks in which each and every block is encrypted by the data owner. We try to apply Hash Message Authentication Code (HMAC) Algorithm for generating hash codes for individual blocks.The data user tries to access the fileby sending request to the all individual edge nodes controlled by cloud server. The cloud server and its associate edges need to giveaccess permissions to the requested users in order to view the file in a decrypted manner. Those who don’t have access permission from multi level cannot be viewed in a plain text manner. Keywords: Edge Server, Hash Message Authentication Code (HMAC), Multi-Layer Approach, Encryption, Decryption, Sensitive Data.